GROWING VANAME SHRIMP (LITOPENAEUS VANNAMEI) USING BIOFLOC Tarpaulin IN LEYEUN VILLAGE, LEUPUNG ACEH BESAR - Gunawan; Muhammadar; Adli Waliul Perdana; Siska Mellisa; Dedi Fazriansyah Putra; Muhammad Irham; Edy Miswar; Nur Fadli; Iko Imelda Arisa; Iswandi; Rahmi (Jurnal Pengabdian Bangsa, 2023)
This training aims to increase the knowledge of vaname shrimp farmers in Lenyeun Village, Leupung, Aceh Besar in rearing using bofolx tarpaulin. The focus is on basic cultivation principles, quality seeds, water management, feeding, and pond environment. The training involves lectures, interactive discussions, and practice in the field. Participants have the opportunity to observe and participate in direct practicum. The hope is that they will be able to apply enlargement techniques and optimize bofolx tarpaulins in cultivation. The ultimate goal is to increase vaname shrimp production in the village, providing a positive impact on the economy and welfare of the local community. Key words: training, vaname shrimp rearing, bofolx tarpaulin, Lenyeun Village, Leupung, Aceh Besar, cultivation, shrimp production.